Assessing the consumption of Giant-Jewel Beetles (Sternocera Orissa) among rural households in the Lepelle-Nkumpi Local Municipality of Limpopo Province - Ntsoane, Mahlogonolo Ramatsimele (My University, 2025)
In the dry regions of Limpopo Province, South Africa, food security remains a significant issue for many rural households due to the challenges of traditional agriculture and limited access to diverse protein sources. The Lepelle-Nkumpi Local Municipality, which is mainly characterised by its pastoral economy, faces critical socio-economic conditions that restrict the nutritional well-being of the households. In this context, the consumption of edible insects, specifically Giant-Jewel Beetles (Sternocera orissa), emerges as a viable alternative protein source. Edible insects are not only rich in protein and essential nutrients but also have a lower environmental impact compared to conventional livestock production, making them a sustainable food option. This study examined the consumption of Giant-Jewel Beetles among rural households in the Lepelle-Nkumpi Local Municipality of Limpopo Province, South Africa. The research objectives were to identify demographic characteristics of the households, profile the consumption frequency of Giant-Jewel Beetles, and analyse socio-economic factors influencing this consumption, employing Descriptive statistics and a Logistic Regression Model. The results revealed that a significant proportion of respondents (44%) were consuming Giant-Jewel Beetles 1-2 times per week, primarily as a relish. The results from the Logistic Regression Model provided insights into the factors influencing the consumption of GJBs in the study area. The Logistic Regression results indicated that factors such as age, food expenditure, reasons for consumption, and potential risks of Giant-Jewel Beetles significantly influence the consumption of Giant-Jewel Beetles. The analysis indicated that older individuals were more likely to consume these insects, while higher food expenditure negatively correlates with their consumption. Based on the findings of the study, there is a need for strategies that promote edible insects as an affordable protein source. Policy makers should consider initiatives that support small-scale insect farming and local value chains, which will enhance the accessibility and affordability of Giant-Jewel Beetles. Additionally, establishing food safety standards for the harvesting and processing of edible insects is important to ensure consumer confidence and mitigate potential health risks.
Thesis (M. Sc. Agriculture (Agricultural Economics)) -- University of Limpopo, 2025
Keywords: Consumption; Entomophagy; Edible Insects; Food security; Giant-jewel beetles; Rural households; Edible insects; Entomophagy; Food security -- Climatic factors; Beetles